Metamorphic P–T evolution of high‐pressure eclogites from garnet growth and reaction textures: Insights from the Kaghan Valley transect, northern Pakistan. (4th January 2013) - Rehman, Hafiz Ur; Yamamoto, Hiroshi; Shin, Keijiro
Abstract The Himalayan Metamorphic Belt of the Kaghan Valley transect in northern Pakistan is a key area where rocks of the Indian Plate have been subducted to greater depths >100 km beneath the Asian Plate and experienced high‐ to ultrahigh‐pressure metamorphism. At least three distinct metamorphic events can be recognized in the metamorphosed mafic rock units (eclogites and amphibolitized eclogites) of the Kaghan Valley: (i) prograde; (ii) peak; and (iii) retrograde stages. Chemical composition, zoning pattern and inclusions in garnet, and metamorphic reactions among major mineral assemblage (garnet + clinopyroxene + quartz + amphibole + epidote) show that core portions of garnet grew under the prograde stage, whereas most of the middle portions were developed or recrystallized under the high‐pressure stage with P–T conditions at 2.3 ± 0.4 GPa and 766 ± 107°C. The rim portions of garnet in association with amphibole and presence of symplectites indicate amphibole‐eclogite to amphibolite‐facies (retrograde) stage with average P–T conditions at 1.5 ± 0.2 GPa and 710 ± 75°C. Zoning in garnet shows Ca‐poor wider cores, Ca‐rich thin middle portions, and chlorite and amphibole development along the outermost rims, suggesting prograde growth at cores and homogenous middle portions and retrogressive formation at rims during the amphibolite‐facies stage. These features suggest that most of the garnet grew during subduction of the Indian Plate lithosphere before the India–Asia collision, whereas rim portions developed during rapid exhumation in the post‐collision stage.